Online trade platforms: Hosting, selling, or both? - Simon Anderson; Özlem Bedre-Defolie (International Journal of Industrial Organization, 2022)
We illustrate conditions under which a trade platform selling its own products alongside third-party sellers benefits or harms consumers. This benefits consumers by lowering prices in a suite of models: a gatekeeper platform facing a competitive fringe of sellers, when fringe sellers also have their own channels perfectly or imperfectly substitutable to the platform; when the gatekeeper platform with fringe sellers competes against a big seller with market power on a differentiated alternative channel; and when the gatekeeper platform hosts only a big seller with market power. Platform product entry might harm consumers when a big firm sells both on the platform and on its alternative channel. The platform selling its own products harms consumers when consumers have heterogenous tastes for variants of products and the platform can control the access of fringe sellers via its commission and own product price. We also review the recent literature to highlight other channels via which benefits and harm arise from the platform selling its own products in its marketplace.
Keywords: D42; L12; L13; L40; H25; 330; Trade platform; Steering; Hybrid business model; Regulation